2011
DOI: 10.1371/journal.pone.0023582
|View full text |Cite
|
Sign up to set email alerts
|

Flanking Bases Influence the Nature of DNA Distortion by Platinum 1,2-Intrastrand (GG) Cross-Links

Abstract: The differences in efficacy and molecular mechanisms of platinum anti-cancer drugs cisplatin (CP) and oxaliplatin (OX) are thought to be partially due to the differences in the DNA conformations of the CP and OX adducts that form on adjacent guanines on DNA, which in turn influence the binding of damage-recognition proteins that control downstream effects of the adducts. Here we report a comprehensive comparison of the structural distortion of DNA caused by CP and OX adducts in the TGGT sequence context using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
(191 reference statements)
2
17
0
Order By: Relevance
“…The current MD studies on platinated-DNA for cisplatin and oxaliplatin did not indicate significant hydrogen-bond patterns on the 5'-side of the platinum adduct (similar to the earlier results presented by Howell [19] and Chaney [21]). However, as shown in Figure 2S, we identified two different hydrogen-bonding patterns on the 3'-side of the platinum-DNA with cisplatin and oxaliplatin.…”
Section: Percentage (%) Occupancy Of Hydrogen-bonds Between Base Pairssupporting
confidence: 90%
See 2 more Smart Citations
“…The current MD studies on platinated-DNA for cisplatin and oxaliplatin did not indicate significant hydrogen-bond patterns on the 5'-side of the platinum adduct (similar to the earlier results presented by Howell [19] and Chaney [21]). However, as shown in Figure 2S, we identified two different hydrogen-bonding patterns on the 3'-side of the platinum-DNA with cisplatin and oxaliplatin.…”
Section: Percentage (%) Occupancy Of Hydrogen-bonds Between Base Pairssupporting
confidence: 90%
“…In a recent study, Chaney et al reported combined NMR and MD data for cisplatin-DNA and oxaliplatin-DNA (using the same sequence as used in this study) [21]. From the MD studies, no hydrogen-bond contacts were identified between platinum ligands and the 5'-DNA bases; whereas hydrogen-bond contacts between platinum ligands and the 3'-DNA bases were identified.…”
Section: Molecular Dynamics Studies On Platinum-dna Adductsmentioning
confidence: 88%
See 1 more Smart Citation
“…Monoubiquitination of PCNA on Lys164 recruits TLS polymerases through a combination of protein-protein interacting motifs that include PCNA-interacting peptide and ubiquitin-binding domains. TLS polymerases possess accommodating active sites and are capable of replicating DNA containing bulky DNA lesions, even when the DNA template is distorted by adducts such as those created by cisplatin (Alt et al, 2007;Waters et al, 2009;Washington et al, 2010;Bhattacharyya et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly interesting since it is observed 70% of GG sites and 20% of GA sites 3 in the DNA cancer cells. RMN studies and molecular dynamic simulation suggest that the Pt-GG DNA adduct modifies the structural properties of mutated DNA allowing the incorporation of the mismatch repair protein 16 . In Cu(II)-nucleobases interactions 17 , Adenine uses N3 atom to coordinate the divalent metal ion while Guanine uses N7 atom, evidencing the capability of the latter one to form metal-Guanine clusters in a similar configuration as the Guanine quartets observed in DNA 8,[18][19] , where interactions WC/H with cis glycosidic bond characterize the formation of hydrogen bonds amongst the purines, involving 4 molecules of Guanine.…”
Section: Introductionmentioning
confidence: 99%